2016
DOI: 10.1002/2016jd025303
|View full text |Cite
|
Sign up to set email alerts
|

Convective cloud vertical velocity and mass‐flux characteristics from radar wind profiler observations during GoAmazon2014/5

Abstract: A radar wind profiler data set collected during the 2 year Department of Energy Atmospheric Radiation Measurement Observations and Modeling of the Green Ocean Amazon (GoAmazon2014/5) campaign is used to estimate convective cloud vertical velocity, area fraction, and mass flux profiles. Vertical velocity observations are presented using cumulative frequency histograms and weighted mean profiles to provide insights in a manner suitable for global climate model scale comparisons (spatial domains from 20 km to 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
117
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(151 citation statements)
references
References 67 publications
15
117
1
3
Order By: Relevance
“…This is likely associated with crystal orientation by the electrical field as more lightning occurs (see Williams et al, 2002), and more vertically oriented ice shapes such as graupel may occur during the dry season than the wet season. The KDP distribution shows considerably larger values in the warm layer during the dry compared to the wet season, indicating that the higher RRs and greater number of positive values in the mixed phase are probably associated with intense updrafts, as shown by Giangrande et al (2016). The correlation coefficient highlights an interesting feature.…”
Section: Cloud Vertical Profiles For the Dry And Wet Seasonsmentioning
confidence: 76%
See 2 more Smart Citations
“…This is likely associated with crystal orientation by the electrical field as more lightning occurs (see Williams et al, 2002), and more vertically oriented ice shapes such as graupel may occur during the dry season than the wet season. The KDP distribution shows considerably larger values in the warm layer during the dry compared to the wet season, indicating that the higher RRs and greater number of positive values in the mixed phase are probably associated with intense updrafts, as shown by Giangrande et al (2016). The correlation coefficient highlights an interesting feature.…”
Section: Cloud Vertical Profiles For the Dry And Wet Seasonsmentioning
confidence: 76%
“…Two different PARSIVEL disdrometers were used during the entire campaign: one during the CHUVA project from January to September 2014 and another, the ARM (Atmospheric Radiation Measurement), from September 2014 to October 2015. Raindrops larger than 5 mm were eliminated from the dataset to best match the co-located rain gauge accumulated rainfall, and a complementary filter was applied as described by Giangrande et al (2016). The drop size distribution (DSD) and all respective rainfall rates (RRs, in mm h −1 ) and mass-weighted mean diameters (D m , in mm) were obtained in 5 min intervals for periods during which RR ≥ 0.5 mm h −1 , as suggested by Tokay et al (2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, practical hazards and operational costs have resulted in a valuable, but limited, dataset (e.g., Byers and Braham, 1948;LeMone and Zipser, 1980;Donner et al, 2001). Recent studies using profiling Doppler radars have suggested an ability to retrieve vertical velocities in convective clouds with an uncertainty of the order of 1-2 m s −1 , thus offering a viable substitute for in situ aircraft measurements (Jorgensen and LeMone, 1989;Cifelli and Rutledge, 1994;May and Rajopadhyaya, 1999;Williams, 2012;Heymsfield et al, 2010;Giangrande et al, 2013a;Kumar et al, 2015;Giangrande et al, 2016). Furthermore, profiling radars provide a high degree of detail of convective clouds in time and height, and can sample even the most intense convective cores.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated multi-Doppler wind retrieval uncertainties by identifying or utilizing (i) the importance of Doppler radar measurement errors and beam geometry (e.g., Doviak et al, 1976;Nelson and Brown, 1987;Matejka and Bartels, 1998;Bousquet et al, 2008), (ii) the influence of radar data objective analysis (e.g., Clark et al, 1980;Gal-Chen, 1982;Testud and Chong, 1983;Given and Ray, 1994;Majcen et al, 2008;Shapiro et al, 2010;Collis et al, 2010), and (iii) OSSEs (e.g., Fanyou and Jietai, 1994;Gao et al, 1999;Liou and Chang, 2009;Potvin et al, 2012b;Potvin and Wicker, 2012). However, few studies have compared practical retrieval performance to other independent air motion estimates from aircraft or ground-based profiling radars (e.g., Collis et al, 2013;Newsom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%